In-situ whisker reinforced aerogel thermal insulation composite material and preparation method thereof
By generating crystal beards in situ on the surface of the fiber surface and the introduction of alumina-silicon gas gel with solution-gel method, the problem of insufficient mechanical performance of the existing oxide gas gel composite material has been solved, and the high ratio and resistance are achieved. High -temperature gas gel insulation composite materials are suitable for aerospace fields.
Patent Information
- Application Number
- CN202411676834.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-11-22
AI Technical Summary
While maintaining thermal insulation properties, existing oxide aerogel composites are difficult to meet the new demands for high pressure performance and toughness in aerospace and other fields.
By generating crystal beards in situ on the surface of the fiber surface, the solution-gel method is used to uniformly introduce aluminum-oxide gas gels into fibers, increasing the combination of air gel and fiber Mechanical performance.
The low -density, low thermal guidance, high -ratio strength and high temperature resistant gas gel insulation composite materials are suitable for thermal protection materials in the aerospace field.
Smart Images

Figure CN119161201B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of aerogel composite materials, and particularly relates to an in-situ whisker-reinforced aerogel thermal insulation composite material and a preparation method thereof. Background Art
[0002] Aerogel is a material with high porosity, low density, high specific surface area and unique nanoporous structure. The lowest room temperature thermal conductivity reaches 0.012W / (m·K). It is a new type of thermal insulation material with excellent performance. Oxide (silicon oxide, aluminum oxide, etc.) aerogels have the characteristics of high temperature resistance, low thermal conductivity, stable physical and chemical properties, but they have intrinsic brittleness and high porosity, and low strength and are difficult to be used directly as thermal insulation materials. Therefore, fibers are usually used as reinforcement phases to prepare aerogel composites, which can effectively improve the mechanical properties of aerogels. For example, the compressive strength (10% strain) and flexural strength of mullite fiber reinforced silica aerogel composites are 0.98MPa and 1.31MPa respectively. Aerogel composites are gradually being used in aerospace and other fields as high-temperature thermal insulation materials.
[0003] However, the rapid development of aerospace, industrial furnaces and other fields has put forward new demands on thermal insulation materials, requiring them to have good pressure bearing performance and toughness while maintaining excellent temperature resistance and thermal insulation performance. Existing oxide aerogel composites have good thermal insulation properties, but the corresponding mechanical properties are limited and it is difficult to meet new demands. Increasing the density of aerogel composites can improve the mechanical strength to a certain extent, but it will inevitably cause changes in the structure and performance of the composite material, which will have an adverse effect on its lightness and thermal insulation performance.
[0004] Therefore, developing a technology that can maintain the thermal insulation performance of aerogel composites while improving the mechanical properties has become an important research direction at present. Summary of the invention
[0005] In view of the problem that in the prior art, the mechanical strength can be improved to a certain extent by increasing the density of aerogel composite materials, but it inevitably causes changes in the structure and performance of the composite materials, which has an adverse effect on their lightness and thermal insulation properties, the present invention provides an in-situ whisker-reinforced aerogel thermal insulation composite material and a preparation method thereof. The in-situ whisker-reinforced aerogel thermal insulation composite material prepared by the present invention has low density, low thermal conductivity, high specific strength, and high temperature resistance, and can be used as a thermal protection material in the aerospace field.
[0006] The technical solution of the present invention is as follows:
[0007] The preparation method of the invention comprises six steps: fiber etching, whisker modified fiber, sol preparation and impregnation, aging, supercritical drying and high-temperature sintering.
[0008] The invention prepares an aerogel thermal insulation composite material with high specific strength through fiber etching, whisker-modified fiber, sol preparation and impregnation, aging, supercritical drying and high-temperature sintering. The ceramic fiber is modified with alumina-silicon oxide composite aerogel, whiskers are generated in situ on the fiber surface, the interface bonding force between the aerogel and the fiber is increased, and the mechanical properties of the aerogel thermal insulation composite material are significantly improved.
[0009] The purpose of the present invention is achieved through the following technical solutions:
[0010] A method for preparing an in-situ whisker-reinforced aerogel thermal insulation composite material comprises the following steps:
[0011] 1) Fiber etching:
[0012] Soak the fiber in an acid solution and keep stirring at 40-80°C for 1-24 hours; take out the fiber, soak it in water and keep stirring at 40-80°C for 6-24 hours; soak the fiber in an alkaline solution and keep stirring at 40-80°C for 1-24 hours; take out the fiber, soak it in water and keep stirring at 40-80°C for 6-24 hours;
[0013] The soaked fibers are placed at 100-200° C. for 4-16 hours until the weight is constant, thereby obtaining pretreated fibers;
[0014] The fiber is selected from one of quartz, alumina, mullite and zirconia;
[0015] The acid solution is one of hydrochloric acid, nitric acid, sulfuric acid and hydrofluoric acid solution, with a mass fraction of 0.5-5%;
[0016] The alkaline solution is a sodium hydroxide solution or a potassium hydroxide solution, with a mass fraction of 0.5 to 5%;
[0017] 2) Whisker modified fiber:
[0018] Aluminum sol, silica sol and catalyst are uniformly mixed to form aluminum-silica sol, and the aluminum-silica sol is impregnated into the pores of the pretreated fiber under a pressure of -0.1 to 0 MPa for 0.5 to 3 hours to obtain a sol-fiber mixture I;
[0019] The aluminum sol has a solvent of water and an average particle size of 5 to 25 nm; the silica sol has a solvent of water and an average particle size of 5 to 20 nm; the catalyst is selected from aluminum fluoride or ammonium molybdate; the molar ratio of aluminum, silicon and catalyst in the aluminum-silica sol is 3:1:(0.001 to 0.01);
[0020] The obtained sol-fiber mixture I is kept at 40-75° C. for 4-16 hours to form a gel-fiber complex I, and the gel-fiber complex I is kept at 120-250° C. for 6-20 hours to obtain an aerogel-fiber complex;
[0021] The obtained aerogel-fiber composite is placed in a high-temperature furnace, heated from room temperature to 900-1200°C at a heating rate of 1-20°C / min, maintained for 1-10 hours, and cooled naturally to obtain whisker-modified fibers;
[0022] 3) Sol preparation and impregnation:
[0023] Under a pressure of -0.1 to 0 MPa, the oxide sol is impregnated into the obtained whisker-modified fiber for 0.5 to 3 hours to obtain a sol-fiber mixture II;
[0024] The oxide sol is one of silicon oxide sol, aluminum oxide sol and zirconium oxide sol;
[0025] The oxide sol, wherein the solvent used is one of methanol, ethanol, isopropanol, n-propanol, n-butanol, sec-butanol, and tert-butanol;
[0026] 4) Aging:
[0027] The obtained sol-fiber mixture II is maintained at 40 to 75° C. for 6 to 24 hours to form a gel-fiber complex;
[0028] 5) Supercritical drying:
[0029] The obtained gel-fiber composite is placed in an autoclave, and after adding alcohol, it is kept sealed, heated to above the critical point of the alcohol and kept for 2 to 10 hours, and the gas in the autoclave is slowly discharged until the pressure is 0, thereby obtaining a modified fiber-reinforced aerogel composite material;
[0030] The alcohol is one of methanol, ethanol, isopropanol, n-propanol, n-butanol, sec-butanol and tert-butanol, and the volume ratio of the alcohol to the gel-fiber complex is 1:(0.5-1);
[0031] 6) High temperature sintering:
[0032] The obtained modified fiber reinforced aerogel composite material is placed in a high temperature furnace, heated from room temperature to 700-1200°C at a heating rate of 1-5°C / min, and maintained for 0.5-8h, and naturally cooled to obtain an in-situ whisker reinforced aerogel thermal insulation composite material. The in-situ whisker reinforced aerogel thermal insulation composite material has the following properties:
[0033] ① The silica aerogel thermal insulation composite material prepared with mullite whisker modified quartz fiber as the reinforcement phase has a volume shrinkage of 0.3-1.7% and a density of 0.29-0.30 g / cm after heat treatment at 900℃ for 2h. 3 The thermal conductivity at room temperature and 900℃ are 0.021-0.022 W / (m·K) and 0.037-0.040 W / (m·K), respectively. The compressive strength (5% strain) is 0.83-0.96MPa, and the tensile strength is 3.2-3.7 MPa.
[0034] ② The alumina aerogel thermal insulation composite material prepared with mullite whisker modified mullite fiber as the reinforcement phase has a volume shrinkage of 0.2-1.1% and a density of 0.29 g / cm after heat treatment at 1200℃ for 2h. 3 The thermal conductivity at room temperature and 1200℃ are 0.025-0.027 W / (m·K) and 0.064-0.069 W / (m·K), respectively. The compressive strength (5% strain) is 1.1-1.4 MPa, and the tensile strength is 2.8-3.4 MPa.
[0035] ③ The silica aerogel thermal insulation composite material prepared with mullite whisker modified zirconia fiber as the reinforcement phase has a volume shrinkage of 1.3-1.7% and a density of 0.32-0.33 g / cm after heat treatment at 900℃ for 2h. 3 The thermal conductivity at room temperature and 900℃ are 0.021-0.022 W / (m·K) and 0.029-0.031W / (m·K) respectively, the compressive strength (5% strain) is 0.9-1.0 MPa, and the tensile strength is 2.4-2.6 MPa.
[0036] In the present invention:
[0037] The solvent described in step 3) is preferably methanol or ethanol; the alcohol described in step 5) is preferably methanol or ethanol.
[0038] The present invention also relates to an in-situ whisker reinforced aerogel thermal insulation composite material, which is obtained by the preparation method of the in-situ whisker reinforced aerogel thermal insulation composite material. The in-situ whisker reinforced aerogel thermal insulation composite material has the following properties:
[0039] ① The silica aerogel thermal insulation composite material prepared with mullite whisker modified quartz fiber as the reinforcement phase has a volume shrinkage of 0.3-1.7% and a density of 0.29-0.30 g / cm after heat treatment at 900℃ for 2h. 3The thermal conductivity at room temperature and 900℃ are 0.021-0.022 W / (m·K) and 0.037-0.040 W / (m·K), respectively. The compressive strength (5% strain) is 0.83-0.96MPa, and the tensile strength is 3.2-3.7 MPa.
[0040] ② The alumina aerogel thermal insulation composite material prepared with mullite whisker modified mullite fiber as the reinforcement phase has a volume shrinkage of 0.2-1.1% and a density of 0.29 g / cm after heat treatment at 1200℃ for 2h. 3 The thermal conductivity at room temperature and 1200℃ are 0.025-0.027 W / (m·K) and 0.064-0.069 W / (m·K), respectively. The compressive strength (5% strain) is 1.1-1.4 MPa, and the tensile strength is 2.8-3.4 MPa.
[0041] ③ The silica aerogel thermal insulation composite material prepared with mullite whisker modified zirconia fiber as the reinforcement phase has a volume shrinkage of 1.3-1.7% and a density of 0.32-0.33 g / cm after heat treatment at 900℃ for 2h. 3 The thermal conductivity at room temperature and 900℃ are 0.021-0.022 W / (m·K) and 0.029-0.031W / (m·K) respectively, the compressive strength (5% strain) is 0.9-1.0 MPa, and the tensile strength is 2.4-2.6 MPa.
[0042] Compared with the prior art, the present invention has the following advantages:
[0043] 1. The preparation method of an in-situ whisker-reinforced aerogel thermal insulation composite material described in the present invention is to introduce the precursor of mullite whiskers, alumina-silicon oxide aerogel, into the fiber uniformly through the sol-gel method, so that it is deposited on the fiber surface. Under the dual conditions of high temperature and catalyst, the aerogel forms nanoscale mullite whiskers on the fiber surface. Conventional liquid phase modification methods are prone to uneven introduction, and whiskers cannot grow uniformly in the fiber, which is not conducive to ensuring the modification effect of the whiskers and the uniformity of the material. The sol-gel method can make the precursor and the catalyst uniformly mixed at the atomic scale and can be uniformly fixed and dispersed in the fiber pores, and the whiskers grow and distribute uniformly on the fiber surface.
[0044] 2. The method for preparing an in-situ whisker-reinforced aerogel thermal insulation composite material described in the present invention includes pre-treating the fibers by etching with acid or alkali solutions to remove impurities on the fiber surface and increase the fiber roughness and surface area, thereby enabling mullite whiskers to grow more fully on the fibers and increasing the interfacial bonding force between the aerogel and the fibers, thereby improving the strength of the aerogel thermal insulation composite material.
[0045] The preparation method of an in-situ whisker-reinforced aerogel thermal insulation composite material described in the present invention generates mullite whiskers in situ on the fiber, which, on the one hand, forms a surface with a large roughness, produces a good anchoring and pinning effect, and significantly improves the physical bonding force between the aerogel and the fiber. On the one hand, the specific surface area of the fiber is increased, the contact and action area between the aerogel and the fiber is increased, and the interaction force between the two is increased. The surface of the nano-scale whisker contains rich silanol and aluminum hydroxyl groups, which condense with the hydroxyl groups on the fiber surface to form a strong chemical bond, which plays a good strengthening role. When the aerogel thermal insulation composite material is compressed (compressive and bending loads), the strong interaction between the aerogel, whiskers, and fibers enables it to withstand higher compressive stress; when it is pulled (tensile and bending loads), the whisker-modified fiber is pulled out of the aerogel, which requires overcoming greater friction and consumes more energy than the simple fiber pullout, so it can withstand higher tensile stress and present a tough fracture.
[0046] 3. The preparation method of the in-situ whisker-reinforced aerogel thermal insulation composite material described in the present invention, the bulk thermal conductivity of the dense mullite crystal is low, and the diameter of the in-situ grown mullite whiskers of the present invention is nanometer-level, which can maintain low solid-state thermal conduction. At the same time, the mullite whiskers can play a good infrared shielding role at high temperature, reducing the high-temperature thermal conductivity of the aerogel composite material.
[0047] 4. In the method for preparing an in-situ whisker-reinforced aerogel thermal insulation composite material described in the present invention, nano-scale mullite whiskers form a nano-scale bonding state with aerogel, which plays a good isolating phase role and can reduce the neck contact of aerogel particles, thereby effectively inhibiting the high-temperature sintering of aerogel and improving the temperature resistance of aerogel composite materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0048] Figure 1 is a physical picture of the in-situ whisker reinforced aerogel thermal insulation composite material prepared in Example 2 of the present invention;
[0049] Figure 2 is a compressive stress-strain curve of the in-situ whisker reinforced aerogel thermal insulation composite material prepared in Example 1 of the present invention;
[0050] Figure 3 It is a tensile stress-displacement curve diagram of the in-situ whisker reinforced aerogel thermal insulation composite material prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0051] The present invention is further described in detail below by way of examples, but these examples should not be considered as limiting the present invention.
[0052] Embodiment 1:
[0053] A method for preparing an in-situ whisker-reinforced aerogel thermal insulation composite material comprises the following steps:
[0054] 1) Fiber etching:
[0055] Immerse the quartz fiber in a hydrochloric acid solution (mass fraction 1.5%) and stir at 60℃ for 8h; take out the fiber and immerse it in water and stir at 65℃ for 12h; soak the fiber in a sodium hydroxide solution (mass fraction 2.4%) and stir at 60℃ for 10h; take out the fiber and immerse it in water and stir at 55℃ for 12h;
[0056] The soaked fiber is placed at 150° C. for 12 hours until constant weight is obtained to obtain pretreated quartz fiber;
[0057] 2) Whisker modified fiber:
[0058] Aluminum sol, silica sol and aluminum fluoride are uniformly mixed to form aluminum-silica sol, and the aluminum-silica sol is impregnated into the pores of the pretreated quartz fiber under a pressure of -0.1 MPa for 2 hours to obtain a sol-fiber mixture I;
[0059] The solvent of the aluminum sol is water, and the average particle size is 15nm; the solvent of the silica sol is water, and the average particle size is 10nm; the molar ratio of aluminum, silicon and catalyst in the aluminum-silica sol is 3:1:0.005;
[0060] The obtained sol-fiber mixture I is kept at 55° C. for 12 hours to form a gel-fiber complex I, and the gel-fiber complex I is kept at 160° C. for 14 hours to obtain an aerogel-fiber complex;
[0061] The obtained aerogel-fiber composite was placed in a high-temperature furnace, heated from room temperature to 950°C at a heating rate of 10°C / min, maintained at that temperature for 4 hours, and cooled naturally to obtain whisker-modified quartz fibers;
[0062] 3) Sol preparation and impregnation:
[0063] Under a pressure of -0.1 MPa, the silica sol was immersed in the whisker-modified quartz fiber for 2 h to obtain a sol-fiber mixture II.
[0064] The silicon oxide sol, wherein the solvent used is ethanol;
[0065] 4) Aging:
[0066] The obtained sol-fiber mixture II was maintained at 65°C for 18 h to obtain a gel-fiber composite;
[0067] 5) Supercritical drying:
[0068] The gel-fiber composite is placed in an autoclave, and after adding ethanol, it is kept airtight, heated to above the critical point of ethanol and kept for 6 hours, and the gas in the autoclave is slowly discharged until the pressure is 0, thereby obtaining a modified fiber-reinforced aerogel composite material;
[0069] The volume ratio of ethanol to gel-fiber complex was 1:0.8;
[0070] 6) High temperature sintering:
[0071] The obtained modified fiber reinforced aerogel composite material was placed in a high temperature furnace, heated from room temperature to 850°C at a heating rate of 4°C / min, maintained for 4 hours, and cooled naturally to obtain a mullite whisker reinforced silica aerogel thermal insulation composite material;
[0072] The mullite whisker reinforced silica aerogel thermal insulation composite material has the following properties:
[0073] After heat treatment at 900℃ for 2h, the volume shrinkage is 1.7% and the density is 0.30 g / cm 3 The thermal conductivity at room temperature and 900℃ are 0.021 W / (m·K) and 0.037 W / (m·K) respectively, the compressive strength (5% strain) is 0.83 MPa, and the tensile strength is 3.2 MPa.
[0074] Embodiment 2:
[0075] A method for preparing an in-situ whisker-reinforced aerogel thermal insulation composite material comprises the following steps:
[0076] 1) Fiber etching:
[0077] Soak the mullite fiber in a hydrochloric acid solution (mass fraction 1.2%), keep stirring at 70℃ for 8h; take out the fiber, soak it in water, keep stirring at 75℃ for 8h; soak the fiber in a potassium hydroxide solution (mass fraction 2.0%), keep stirring at 65℃ for 10h; take out the fiber, soak it in water, keep stirring at 75℃ for 12h;
[0078] The soaked fibers were placed at 150° C. for 12 hours until constant weight was obtained to obtain pretreated mullite fibers;
[0079] 2) Whisker modified fiber:
[0080] Aluminum sol, silica sol and ammonium molybdate are uniformly mixed to form aluminum-silica sol, and the aluminum-silica sol is impregnated into the pores of the pretreated mullite fiber under a pressure of -0.1 MPa for 1.5 hours to obtain a sol-fiber mixture I;
[0081] The solvent of the aluminum sol is water, and the average particle size is 20nm; the solvent of the silica sol is water, and the average particle size is 15nm; the molar ratio of aluminum, silicon and catalyst in the aluminum-silica sol is 3:1:0.006;
[0082] The obtained sol-fiber mixture I is kept at 60° C. for 10 hours to form a gel-fiber complex I, and the gel-fiber complex I is then kept at 180° C. for 12 hours to obtain an aerogel-fiber complex;
[0083] The obtained aerogel-fiber composite was placed in a high-temperature furnace, heated from room temperature to 1000°C at a heating rate of 15°C / min, maintained for 4 hours, and cooled naturally to obtain whisker-modified mullite fiber;
[0084] 3) Sol preparation and impregnation:
[0085] Under a pressure of -0.1 MPa, the alumina sol was impregnated into the whisker-modified mullite fiber for 2 h to obtain a sol-fiber mixture II;
[0086] The alumina sol, wherein the solvent used is isopropanol;
[0087] 4) Aging:
[0088] The obtained sol-fiber mixture II was maintained at 70°C for 16 h to obtain a gel-fiber composite;
[0089] 5) Supercritical drying:
[0090] The gel-fiber composite is placed in an autoclave, isopropanol is added and kept sealed, heated to above the critical point of isopropanol and kept for 4 hours, and the gas in the autoclave is slowly discharged until the pressure is 0, thereby obtaining a modified fiber-reinforced aerogel composite material;
[0091] The volume ratio of isopropanol to gel-fiber complex was 1:0.6;
[0092] 6) High temperature sintering:
[0093] The obtained modified fiber reinforced aerogel composite material was placed in a high temperature furnace, heated from room temperature to 1100°C at a heating rate of 3°C / min, maintained for 4 hours, and cooled naturally to obtain a mullite whisker reinforced alumina aerogel thermal insulation composite material;
[0094] The mullite whisker reinforced alumina aerogel thermal insulation composite material has the following properties:
[0095] After heat treatment at 1200℃ for 2h, the volume shrinkage is 1.1% and the density is 0.29 g / cm 3The thermal conductivity at room temperature and 1200℃ are 0.025 W / (m·K) and 0.064 W / (m·K) respectively, the compressive strength (5% strain) is 1.1 MPa, and the tensile strength is 2.8 MPa.
[0096] Embodiment 3:
[0097] A method for preparing an in-situ whisker-reinforced aerogel thermal insulation composite material comprises the following steps:
[0098] 1) Fiber etching:
[0099] The zirconium oxide fiber was immersed in a hydrochloric acid solution (mass fraction 1.5%) and stirred at 70°C for 8 hours; the fiber was taken out and immersed in water and stirred at 75°C for 8 hours; the fiber was immersed in a sodium hydroxide solution (mass fraction 2.0%) and stirred at 65°C for 10 hours; the fiber was taken out and immersed in water and stirred at 75°C for 12 hours;
[0100] The soaked fibers were placed at 180° C. and maintained for 10 hours until constant weight was obtained to obtain pretreated zirconia fibers;
[0101] 2) Whisker modified fiber:
[0102] Aluminum sol, silica sol and ammonium molybdate are uniformly mixed to form aluminum-silica sol, and the aluminum-silica sol is impregnated into the pores of the pretreated zirconia fiber under a pressure of -0.05 MPa for 2 hours to obtain a sol-fiber mixture I;
[0103] The solvent of the aluminum sol is water, and the average particle size is 15nm; the solvent of the silica sol is water, and the average particle size is 8nm; the molar ratio of aluminum, silicon and catalyst in the aluminum-silica sol is 3:1:0.004;
[0104] The obtained sol-fiber mixture I is kept at 60° C. for 10 hours to form a gel-fiber complex I, and the gel-fiber complex I is then kept at 180° C. for 12 hours to obtain an aerogel-fiber complex;
[0105] The obtained aerogel-fiber composite was placed in a high-temperature furnace, heated from room temperature to 900°C at a heating rate of 8°C / min, maintained for 6 hours, and cooled naturally to obtain whisker-modified zirconia fibers;
[0106] 3) Sol preparation and impregnation:
[0107] Under a pressure of -0.05 MPa, silica sol was impregnated into whisker-modified zirconia fibers for 1.5 h to obtain a sol-fiber mixture II.
[0108] The silicon oxide sol, wherein the solvent used is methanol;
[0109] 4) Aging:
[0110] The obtained sol-fiber mixture II was kept at 50°C for 20 h to obtain a gel-fiber composite;
[0111] 5) Supercritical drying:
[0112] The gel-fiber composite is placed in an autoclave, and after adding methanol, it is kept airtight, heated to above the critical point of methanol and kept for 4 hours, and the gas in the autoclave is slowly discharged until the pressure is 0, thereby obtaining a modified fiber-reinforced aerogel composite material;
[0113] The volume ratio of methanol to gel-fiber complex was 1:0.5;
[0114] 6) High temperature sintering:
[0115] The obtained modified fiber reinforced aerogel composite material was placed in a high temperature furnace, heated from room temperature to 800°C at a heating rate of 3°C / min, maintained for 5 hours, and cooled naturally to obtain a mullite whisker reinforced silica aerogel thermal insulation composite material;
[0116] The mullite whisker reinforced silica aerogel thermal insulation composite material has the following properties:
[0117] After heat treatment at 900℃ for 2h, the volume shrinkage is 1.3% and the density is 0.32 g / cm 3 The thermal conductivity at room temperature and 900℃ are 0.022 W / (m·K) and 0.031 W / (m·K) respectively, the compressive strength (5% strain) is 1.0 MPa, and the tensile strength is 2.6 MPa.
[0118] Embodiment 4:
[0119] A method for preparing an in-situ whisker-reinforced aerogel thermal insulation composite material comprises the following steps:
[0120] 1) Fiber etching:
[0121] The quartz fiber was immersed in a nitric acid solution (mass fraction 5.0%) and stirred at 40℃ for 24h; the fiber was taken out and immersed in water and stirred at 80℃ for 6h; the fiber was immersed in a sodium hydroxide solution (mass fraction 5.0%) and stirred at 80℃ for 1h; the fiber was taken out and immersed in water and stirred at 40℃ for 24h;
[0122] The soaked fiber is placed at 200°C for 4 hours until constant weight is obtained to obtain pretreated quartz fiber;
[0123] 2) Whisker modified fiber:
[0124] Aluminum sol, silica sol and aluminum fluoride are uniformly mixed to form aluminum-silica sol, and the aluminum-silica sol is impregnated into the pores of the pretreated quartz fiber under a pressure of 0 MPa for 3 hours to obtain a sol-fiber mixture I;
[0125] The solvent of the aluminum sol is water, and the average particle size is 22nm; the solvent of the silica sol is water, and the average particle size is 18nm; the molar ratio of aluminum, silicon and catalyst in the aluminum-silica sol is 3:1:0.01;
[0126] The obtained sol-fiber mixture I is kept at 75° C. for 4 hours to form a gel-fiber complex I, and the gel-fiber complex I is kept at 250° C. for 6 hours to obtain an aerogel-fiber complex;
[0127] The obtained aerogel-fiber composite was placed in a high-temperature furnace, heated from room temperature to 1200°C at a heating rate of 20°C / min, maintained for 1 hour, and cooled naturally to obtain whisker-modified quartz fiber;
[0128] 3) Sol preparation and impregnation:
[0129] Under a pressure of -0.1 MPa, the silica sol was immersed in the whisker-modified quartz fiber for 2 h to obtain a sol-fiber mixture II.
[0130] The silicon oxide sol, wherein the solvent used is sec-butyl alcohol;
[0131] 4) Aging:
[0132] The obtained sol-fiber mixture II was maintained at 75°C for 6 h to obtain a gel-fiber composite;
[0133] 5) Supercritical drying:
[0134] The gel-fiber composite is placed in an autoclave, and after adding sec-butyl alcohol, it is kept airtight, heated to above the critical point of sec-butyl alcohol and kept for 10 hours, and the gas in the autoclave is slowly discharged until the pressure is 0, thereby obtaining a modified fiber-reinforced aerogel composite material;
[0135] The volume ratio of ethanol to gel-fiber complex was 1:0.5;
[0136] 6) High temperature sintering:
[0137] The obtained modified fiber reinforced aerogel composite material was placed in a high temperature furnace, heated from room temperature to 700°C at a heating rate of 5°C / min, maintained for 8 hours, and cooled naturally to obtain a mullite whisker reinforced silica aerogel thermal insulation composite material;
[0138] The mullite whisker reinforced silica aerogel thermal insulation composite material has the following properties:
[0139] After heat treatment at 900℃ for 2h, the volume shrinkage is 0.3% and the density is 0.29 g / cm 3 The thermal conductivity at room temperature and 900℃ are 0.022 W / (m·K) and 0.040 W / (m·K) respectively, the compressive strength (5% strain) is 0.96 MPa, and the tensile strength is 3.7 MPa.
[0140] Embodiment 5:
[0141] A method for preparing an in-situ whisker-reinforced aerogel thermal insulation composite material comprises the following steps:
[0142] 1) Fiber etching:
[0143] The mullite fiber was immersed in a hydrofluoric acid solution (mass fraction 0.5%) and stirred at 45°C for 10 hours; the fiber was taken out and immersed in water and stirred at 75°C for 8 hours; the fiber was immersed in a potassium hydroxide solution (mass fraction 2.0%) and stirred at 65°C for 10 hours; the fiber was taken out and immersed in water and stirred at 75°C for 12 hours;
[0144] The soaked fibers were placed at 150° C. for 12 hours until constant weight was obtained to obtain pretreated mullite fibers;
[0145] 2) Whisker modified fiber:
[0146] Aluminum sol, silica sol and ammonium molybdate are uniformly mixed to form aluminum-silica sol, and the aluminum-silica sol is impregnated into the pores of the pretreated mullite fiber under a pressure of -0.1 MPa for 0.5 h to obtain a sol-fiber mixture I;
[0147] The solvent of the aluminum sol is water, and the average particle size is 25nm; the solvent of the silica sol is water, and the average particle size is 20nm; the molar ratio of aluminum, silicon and catalyst in the aluminum-silica sol is 3:1:0.001;
[0148] The obtained sol-fiber mixture I is kept at 60° C. for 10 hours to form a gel-fiber complex I, and the gel-fiber complex I is then kept at 180° C. for 12 hours to obtain an aerogel-fiber complex;
[0149] The obtained aerogel-fiber composite was placed in a high-temperature furnace, heated from room temperature to 1200°C at a heating rate of 20°C / min, maintained for 1 hour, and cooled naturally to obtain whisker-modified mullite fiber;
[0150] 3) Sol preparation and impregnation:
[0151] Under a pressure of -0.1 MPa, the alumina sol was immersed in the whisker-modified mullite fiber for 2 h to obtain a sol-fiber mixture II;
[0152] The alumina sol, wherein the solvent used is n-butanol;
[0153] 4) Aging:
[0154] The obtained sol-fiber mixture II was maintained at 75°C for 4 h to obtain a gel-fiber composite;
[0155] 5) Supercritical drying:
[0156] The gel-fiber composite is placed in an autoclave, and after adding n-butanol, it is kept airtight, heated to above the critical point of n-butanol and kept for 2 hours, and the gas in the autoclave is slowly discharged until the pressure is 0, thereby obtaining a modified fiber-reinforced aerogel composite material;
[0157] The volume ratio of isopropyl alcohol to gel-fiber complex was 1:1;
[0158] 6) High temperature sintering:
[0159] The obtained modified fiber reinforced aerogel composite material was placed in a high temperature furnace, heated from room temperature to 1200°C at a heating rate of 1°C / min, maintained for 0.5h, and cooled naturally to obtain a mullite whisker reinforced alumina aerogel thermal insulation composite material;
[0160] The mullite whisker reinforced alumina aerogel thermal insulation composite material has the following properties:
[0161] After heat treatment at 1200℃ for 2h, the volume shrinkage is 0.2% and the density is 0.29 g / cm 3 The thermal conductivity at room temperature and 1200℃ are 0.027 W / (m·K) and 0.069 W / (m·K) respectively, the compressive strength (5% strain) is 1.4 MPa, and the tensile strength is 3.4 MPa.
[0162] Embodiment 6:
[0163] A method for preparing an in-situ whisker-reinforced aerogel thermal insulation composite material comprises the following steps:
[0164] 1) Fiber etching:
[0165] The zirconium oxide fiber was immersed in a sulfuric acid solution (mass fraction 0.5%) and stirred at 80°C for 6 hours; the fiber was taken out and immersed in water and stirred at 75°C for 8 hours; the fiber was immersed in a sodium hydroxide solution (mass fraction 0.5%) and stirred at 80°C for 1 hour; the fiber was taken out and immersed in water and stirred at 75°C for 12 hours;
[0166] The soaked fibers were placed at 120° C. for 16 hours until constant weight was obtained to obtain pretreated zirconia fibers;
[0167] 2) Whisker modified fiber:
[0168] Aluminum sol, silica sol and ammonium molybdate are uniformly mixed to form aluminum-silica sol, and the aluminum-silica sol is impregnated into the pores of the pretreated zirconia fiber under a pressure of -0.06 MPa for 2 hours to obtain a sol-fiber mixture I;
[0169] The solvent of the aluminum sol is water, and the average particle size is 5nm; the solvent of the silica sol is water, and the average particle size is 5nm; the molar ratio of aluminum, silicon and catalyst in the aluminum-silica sol is 3:1:0.002;
[0170] The obtained sol-fiber mixture I is kept at 60° C. for 10 hours to form a gel-fiber complex I, and the gel-fiber complex I is then kept at 170° C. for 12 hours to obtain an aerogel-fiber complex;
[0171] The obtained aerogel-fiber composite was placed in a high-temperature furnace, heated from room temperature to 900°C at a heating rate of 1°C / min, maintained for 10 hours, and cooled naturally to obtain whisker-modified zirconia fibers;
[0172] 3) Sol preparation and impregnation:
[0173] Under a pressure of -0.05 MPa, the silica sol was impregnated into the whisker-modified zirconia fiber for 1.5 h to obtain a sol-fiber mixture II;
[0174] The silicon oxide sol, wherein the solvent used is n-propanol;
[0175] 4) Aging:
[0176] The obtained sol-fiber mixture II was kept at 50°C for 20 h to obtain a gel-fiber composite;
[0177] 5) Supercritical drying:
[0178] The gel-fiber composite is placed in an autoclave, and after adding n-propanol, it is kept airtight, heated to above the critical point of n-propanol and kept for 4 hours, and the gas in the autoclave is slowly discharged until the pressure is 0, thereby obtaining a modified fiber-reinforced aerogel composite material;
[0179] The volume ratio of methanol to gel-fiber complex was 1:0.9;
[0180] 6) High temperature sintering:
[0181] The obtained modified fiber reinforced aerogel composite material was placed in a high temperature furnace, heated from room temperature to 700°C at a heating rate of 1°C / min, maintained for 8 hours, and cooled naturally to obtain a mullite whisker reinforced silica aerogel thermal insulation composite material;
[0182] The mullite whisker reinforced silica aerogel thermal insulation composite material has the following properties:
[0183] After heat treatment at 900℃ for 2h, the volume shrinkage is 1.7% and the density is 0.33 g / cm 3 The thermal conductivity at room temperature and 900℃ are 0.021 W / (m·K) and 0.029 W / (m·K) respectively, the compressive strength (5% strain) is 0.9 MPa, and the tensile strength is 2.4 MPa.
[0184] Comparative Example 1:
[0185] The difference between Comparative Example 1 and Example 1 is that the mass fraction of the hydrochloric acid solution in step 1) is 0.2%, and the rest is the same as Example 1;
[0186] The obtained aerogel thermal insulation composite material has a compressive strength (5% strain) of 0.73 MPa and a tensile strength of 2.6 MPa.
[0187] It shows that a low mass fraction of hydrochloric acid solution will weaken the etching effect and the surface roughness of the fiber, thus affecting the strength of the aerogel thermal insulation composite material.
[0188] Comparative Example 2:
[0189] The difference between Comparative Example 2 and Example 1 is that in step 1), no alkali solution soaking is performed, and the rest is the same as Example 1;
[0190] The obtained aerogel thermal insulation composite material has a compressive strength (5% strain) of 0.67 MPa and a tensile strength of 2.1 MPa.
[0191] It shows that only using acid solution treatment will weaken the etching effect and the surface roughness of the fiber, thus affecting the strength of the aerogel thermal insulation composite material. Using acid solution and alkaline solution for treatment in sequence can maximize the pretreatment effect.
[0192] Comparative Example 3:
[0193] The difference between Comparative Example 3 and Example 1 is that the average diameters of the aluminum sol and silica sol particles in step 2) are 4 nm and 3 nm respectively, and the rest are the same as in Example 1;
[0194] The obtained aerogel thermal insulation composite material has a volume shrinkage rate of 3.2% after heat treatment at 900°C for 2h.
[0195] It shows that if the average diameter of aluminum sol and silica sol particles is too small, the diameter of the generated mullite whiskers will be too small, the sintering resistance will be reduced, and thus the temperature resistance of the prepared aerogel thermal insulation composite material will be reduced.
[0196] Comparative Example 4:
[0197] The difference between Comparative Example 4 and Example 1 is that the heat treatment temperature of the aerogel-fiber composite in step 2) is 750° C., and the rest is the same as Example 1;
[0198] The obtained aerogel thermal insulation composite material has a compressive strength (5% strain) of 0.56 MPa and a tensile strength of 1.6 MPa.
[0199] It shows that if the heat treatment temperature is too low, it will significantly affect the normal growth of whiskers, thereby affecting the strength of the aerogel thermal insulation composite material.
[0200] Comparative Example 5:
[0201] The difference between Comparative Example 5 and Example 1 is that the heat treatment temperature of the aerogel-fiber composite in step 2) is 1300° C., and the rest is the same as Example 1;
[0202] The thermal conductivity of the obtained aerogel thermal insulation composite material at room temperature and 900°C are 0.026 W / (m·K) and 0.049 W / (m·K), respectively.
[0203] It shows that if the heat treatment temperature is too high, on the one hand, the fiber will be sintered and the solid-state heat conduction of the fiber will be increased; on the other hand, the mullite whiskers will grow too thick and increase the solid-phase heat conduction of the mullite whiskers, thereby increasing the thermal conductivity of the aerogel insulation composite material.
[0204] Comparative Example 6:
[0205] The difference between Comparative Example 6 and Example 1 is that the drying method in step 5) is normal pressure drying, and the rest is the same as Example 1;
[0206] The thermal conductivity of the obtained aerogel thermal insulation composite material at room temperature and 900°C are 0.031 W / (m·K) and 0.048 W / (m·K), respectively.
[0207] The results show that the room temperature drying method will cause the silica aerogel to shrink significantly, making it difficult to maintain a good nanopore structure, and the gaseous heat conduction will increase significantly, thereby significantly increasing the thermal conductivity of the aerogel insulation composite material.
[0208] Comparative Example 7:
[0209] The difference between Comparative Example 7 and Example 1 is that the sintering temperature in step 6) is 600° C., and the rest is the same as Example 1;
[0210] The obtained aerogel thermal insulation composite material has a compressive strength (5% strain) of 0.72 MPa and a tensile strength of 2.7 MPa.
[0211] It shows that if the sintering temperature is too low, the interfacial bonding strength between aerogel and fiber, and between aerogel and whiskers will be affected, thereby reducing the strength of the aerogel thermal insulation composite material.
[0212] Comparative Example 8:
[0213] The difference between Comparative Example 8 and Example 1 is that the sintering temperature in step 6) is 1350° C., and the rest is the same as Example 1;
[0214] The thermal conductivity of the obtained aerogel thermal insulation composite material at room temperature and 1200°C are 0.032 W / (m·K) and 0.085 W / (m·K), respectively.
[0215] It shows that too high sintering temperature will cause the alumina aerogel to sinter significantly, resulting in volume shrinkage and pore structure collapse of the alumina aerogel, and both solid-phase heat conduction and gas-phase heat conduction will increase simultaneously, thereby significantly increasing the thermal conductivity of the aerogel thermal insulation composite material.
[0216] The above are only preferred implementations of the present invention. The protection scope of the present invention is not limited to the above embodiments. Various process schemes that are not substantially different from the concept of the present invention are within the protection scope of the present invention.
Claims
1. A method for preparing an in-situ whisker reinforced aerogel thermal insulation composite material, characterized in that: The following steps are involved: 1) Fiber etching: Soak the fiber in an acid solution and keep stirring at 40-80°C for 1-24 hours; take out the fiber, soak it in water and keep stirring at 40-80°C for 6-24 hours; soak the fiber in an alkaline solution and keep stirring at 40-80°C for 1-24 hours; take out the fiber, soak it in water and keep stirring at 40-80°C for 6-24 hours; The soaked fibers are placed at 100-200° C. for 4-16 hours until the weight is constant, thereby obtaining pretreated fibers; The fiber is selected from one of quartz, alumina, mullite and zirconia; The acid solution is one of hydrochloric acid, nitric acid, sulfuric acid and hydrofluoric acid solution, with a mass fraction of 0.5-5%; The alkaline solution is a sodium hydroxide solution or a potassium hydroxide solution, with a mass fraction of 0.5 to 5%; 2) Whisker modified fiber: Aluminum sol, silica sol and catalyst are uniformly mixed to form aluminum-silica sol, and the aluminum-silica sol is impregnated into the pores of the pretreated fiber under a pressure of -0.1 to 0 MPa for 0.5 to 3 hours to obtain a sol-fiber mixture I; The aluminum sol has a solvent of water and an average particle size of 5 to 25 nm; the silica sol has a solvent of water and an average particle size of 5 to 20 nm; the catalyst is selected from aluminum fluoride or ammonium molybdate; the molar ratio of aluminum, silicon and catalyst in the aluminum-silica sol is 3:1:(0.001 to 0.01); The obtained sol-fiber mixture I is kept at 40-75° C. for 4-16 hours to form a gel-fiber complex I, and the gel-fiber complex I is kept at 120-250° C. for 6-20 hours to obtain an aerogel-fiber complex; The obtained aerogel-fiber composite is placed in a high-temperature furnace, heated from room temperature to 900-1200°C at a heating rate of 1-20°C / min, maintained for 1-10 hours, and cooled naturally to obtain whisker-modified fibers; 3) Sol preparation and impregnation: Under a pressure of -0.1 to 0 MPa, the oxide sol is impregnated into the obtained whisker-modified fiber for 0.5 to 3 hours to obtain a sol-fiber mixture II; The oxide sol is one of silicon oxide sol, aluminum oxide sol and zirconium oxide sol; The oxide sol, wherein the solvent used is one of methanol, ethanol, isopropanol, n-propanol, n-butanol, sec-butanol, and tert-butanol; 4) Aging: The obtained sol-fiber mixture II is maintained at 40 to 75° C. for 6 to 24 hours to form a gel-fiber complex; 5) Supercritical drying: The obtained gel-fiber composite is placed in an autoclave, and after adding alcohol, it is kept sealed, heated to above the critical point of the alcohol and kept for 2 to 10 hours, and the gas in the autoclave is slowly discharged until the pressure is 0, thereby obtaining a modified fiber-reinforced aerogel composite material; The alcohol is one of methanol, ethanol, isopropanol, n-propanol, n-butanol, sec-butanol and tert-butanol, and the volume ratio of the alcohol to the gel-fiber complex is 1:(0.5-1); 6) High temperature sintering: The obtained modified fiber reinforced aerogel composite material is placed in a high temperature furnace, heated from room temperature to 700-1200°C at a heating rate of 1-5°C / min, and maintained for 0.5-8h, and naturally cooled to obtain an in-situ whisker reinforced aerogel thermal insulation composite material. The in-situ whisker reinforced aerogel thermal insulation composite material has the following properties: ① The silica aerogel thermal insulation composite material prepared with mullite whisker modified quartz fiber as the reinforcement phase has a volume shrinkage of 0.3-1.7% and a density of 0.29-0.30 g / cm after heat treatment at 900℃ for 2h. 3 The thermal conductivity at room temperature and 900℃ are 0.021-0.022 W / (m·K) and 0.037-0.040 W / (m·K), respectively. The compressive strength at 5% strain is 0.83-0.96 MPa, and the tensile strength is 3.2-3.7 MPa. ② The alumina aerogel thermal insulation composite material prepared with mullite whisker modified mullite fiber as the reinforcement phase has a volume shrinkage of 0.2-1.1% and a density of 0.29 g / cm after heat treatment at 1200℃ for 2h. 3 The thermal conductivity at room temperature and 1200℃ are 0.025-0.027 W / (m·K) and 0.064-0.069 W / (m·K), respectively. The compressive strength at 5% strain is 1.1-1.4 MPa, and the tensile strength is 2.8-3.4 MPa. ③ The silica aerogel thermal insulation composite material prepared with mullite whisker modified zirconia fiber as the reinforcement phase has a volume shrinkage of 1.3-1.7% and a density of 0.32-0.33 g / cm after heat treatment at 900℃ for 2h. 3 The thermal conductivity at room temperature and 900℃ are 0.021-0.022 W / (m·K) and 0.029-0.031W / (m·K) respectively, the compressive strength with 5% strain is 0.9-1.0 MPa, and the tensile strength is 2.4-2.6 MPa.
2. The method for preparing an in-situ whisker reinforced aerogel thermal insulation composite material according to claim 1, characterized in that: The solvent described in step 3) is methanol or ethanol; the alcohol described in step 5) is methanol or ethanol.
3. An in-situ whisker reinforced aerogel thermal insulation composite material, characterized in that: The in-situ whisker reinforced aerogel thermal insulation composite material is prepared by the method for preparing the in-situ whisker reinforced aerogel thermal insulation composite material according to claim 1 or 2, wherein the in-situ whisker reinforced aerogel thermal insulation composite material has the following properties: ① The silica aerogel thermal insulation composite material prepared with mullite whisker modified quartz fiber as the reinforcement phase has a volume shrinkage of 0.3-1.7% and a density of 0.29-0.30 g / cm after heat treatment at 900℃ for 2h. 3 The thermal conductivity at room temperature and 900℃ are 0.021-0.022 W / (m·K) and 0.037-0.040 W / (m·K), respectively. The compressive strength at 5% strain is 0.83-0.96 MPa, and the tensile strength is 3.2-3.7 MPa. ② The alumina aerogel thermal insulation composite material prepared with mullite whisker modified mullite fiber as the reinforcement phase has a volume shrinkage of 0.2-1.1% and a density of 0.29 g / cm after heat treatment at 1200℃ for 2h. 3 The thermal conductivity at room temperature and 1200℃ are 0.025-0.027 W / (m·K) and 0.064-0.069 W / (m·K), respectively. The compressive strength at 5% strain is 1.1-1.4 MPa, and the tensile strength is 2.8-3.4 MPa. ③ The silica aerogel thermal insulation composite material prepared with mullite whisker modified zirconia fiber as the reinforcement phase has a volume shrinkage of 1.3-1.7% and a density of 0.32-0.33 g / cm after heat treatment at 900℃ for 2h. 3 The thermal conductivity at room temperature and 900℃ are 0.021-0.022 W / (m·K) and 0.029-0.031W / (m·K) respectively, the compressive strength with 5% strain is 0.9-1.0 MPa, and the tensile strength is 2.4-2.6 MPa.
Citation Information
Patent Citations
Preparation method for mullite whisker with high length-diameter ratio by in-situ growth
CN110468453A
Fluoride-free preparation method of mullite fiber whisker reinforcement and aerogel prepared by fluoride-free preparation method
CN112456962A